Revisiting the streptococcal M protein: modern perspectives on antibody function, host interactions, and therapeutic targeting - Wrighton, Sebastian; Nordenfelt, Pontus (Frontiers in Immunology, 2026)
Group A Streptococcus (GAS) causes extensive global morbidity and rising rates of invasive disease, for which clinical outcomes remain poor despite antibiotic treatment of susceptible strains. This limitation of current therapy underscores the need for alternative or adjunctive approaches. Antibody-based interventions represent a promising but underexplored strategy. Historically, the streptococcal M protein was considered an unsuitable therapeutic target due to its sequence variability and concerns about autoreactivity. These perceptions arose largely from early murine hybridoma studies, peptide-based immunizations, and functional assays that disproportionately emphasized hypervariable epitopes. Recent advances now challenge these longstanding views. Improved structural and functional analyses, human monoclonal antibody discovery, and more sensitive measurements of phagocytosis and opsonization demonstrate that conserved regions of M protein can support effective immune engagement. Newly described mechanisms, including dual-Fab binding and antibody-dependent remodeling of the bacterial surface, further reveal unexpected layers of antibody function during GAS infection. This review integrates historical and modern insights into M-protein immunobiology and discusses how antibody engineering may enhance therapeutic activity. We also consider how monoclonal antibodies could be deployed alongside antibiotics and adjunctive treatments. Together, these developments support a reassessment of M protein as a viable target for antibody-based therapies against GAS.